2022
DOI: 10.11591/eei.v11i4.3859
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi's T-method with nearest integer-based binary bat algorithm for prediction

Abstract: Taguchi’s T-method is a new prediction technique under the Mahalanobis-Taguchi system to predict unknown output or future states based on available historical information. Conventionally, in optimizing the T-method prediction accuracy, Taguchi’s orthogonal array is utilized to determine a subset of significant features to be used in formulating the optimal prediction model. This, however, resulted in a sub-optimal prediction accuracy due to its fixed and limited feature combination offered for evaluation and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The factorial effect chart reveals the relative importance of features based on the deterioration of the average integrated estimate SNR (db) of features when it is not used in combination. The detail of the steps is elaborated in [16].…”
Section: Methods 21 Conventional T-methods Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The factorial effect chart reveals the relative importance of features based on the deterioration of the average integrated estimate SNR (db) of features when it is not used in combination. The detail of the steps is elaborated in [16].…”
Section: Methods 21 Conventional T-methods Prediction Modelmentioning
confidence: 99%
“…Studies by [14], [15] that employ an artificial bee colony algorithm and a modified artificial bee colony algorithm to optimize the feature selection process show promising improvement in the T-method prediction accuracy over the conventional OA approach in terms of error rate. In the latest development, [16] reported that integrating the binary Bat algorithm based on the nearest integer binarization scheme with the T-method enhanced the prediction accuracy ranging from 7.2% to 55%, dependent on case studies. In a continuous quest for optimality, the ideal approach is through an exhaustive search approach where every possible combination is assessed and evaluated.…”
Section: Introductionmentioning
confidence: 99%